Stanza - Esbaum, Jill.; Davis, Jack E. (New York : Harcourt Children's Books, 2009)
Stanza the dog and his two rotten brothers terrorize the streets by day, but at night Stanza secretly writes poetry.
2.8
K-3
Keywords: Contests -- Juvenile fiction; Dogs -- Juvenile fiction; Poetry -- Juvenile fiction; Self-realization -- Juvenile fiction; Contests -- Fiction; Dogs -- Fiction; Poetry -- Fiction; Self-realization -- Fiction; Stories in rhyme; Contests -- Fiction; Dogs -- Fiction; Poetry -- Fiction; Self-realization -- Fiction; Stories in rhyme